Бронзова гідрія зі збірки Національного музею історії України - Пукліна, О.О.; Трейстер, М.Ю. (Археологія, 2006)
Статтю присвячено дослідженню ручок бронзової гідрії зі збірки Національного музею історії України. На основі
аналізу аналогічних виробів висунуто гіпотезу про належність фрагментованої бронзової гідрії до ранніх варіантів
гідрій «групи Патр». В статье опубликованы ручки бронзовой гидрии из Национального музея истории Украины. На основании анализа
подобных изделий сделан вывод о принадлежности фрагментированной бронзовой гидрии к ранним вариантам
гидрий «группы Патр». Выдвинута гипотеза о производстве подобных гидрий в мастерских Северного Пелопоннеса во второй половине IV века до н. э. The article publishes the handles of a bronze hydria from the National Museum of History of Ukraine. Basing on the
analysis of similar artifacts a conclusion was made regarding the belonging of the fragmented bronze hydria to the early
variants of the hydria of the «Patras group». A hypothesis was advanced that similar hydria were produced in the workshops
of the Northern Peloponnesus in the second half of the 4th century BC.